Information culture of the Belarusian State University teachers - Kurilovich, Natalia V. (Journal of the Belarusian State University. Sociology, 2024)
The article examines key aspects of studying information culture in modern conditions. It is shown that there is still no unified scientific approach to the understanding of information culture as a social phenomenon. The author considers the interrelation of information culture and functional literacy of a person. It is emphasised that in the context of transformation of all spheres of social life, the requirements to the information culture of a modern person are constantly increasing. The author argues that nowadays information culture is a mandatory component of higher school teacher’ professional competence. The author points out that in the conditions of accelerating higher education digitalisation the importance of university teachers’ information culture will only grow. The positions of specialists on the issue of the structure of higher school teachers’ information culture are investigated. The author identifies and characterises main levels of teacher’s information culture: cognitive, value and behavioural. The article is based on the results of the sociological research «Information culture of the Belarusian State University teachers in the conditions of education digitalisation». The online survey was conducted in the spring of 2023. Based on the materials of the survey, it is revealed that the university teachers evaluate their competences in the sphere of using information and communication technologies and interaction with the information educational environment quite highly. The article considers the perceptions of the Belarusian State University teachers about the main advantages and disadvantages of Internet communication. The article presents the frequency of teachers’ use of information and communication technologies in conducting classes. Special attention is paid to the motivational-value and communicative-ethical components of the Belarusian State University teachers’ information culture.
Keywords: information culture; functional literacy; information literacy; online survey; teachers; Belarusian State University